Assessment of service quality towards customer loyalty: case study of tentrem - Kurniawan, William; Rahmani Qastharin, Annisa (Journal of Business and Management, 2019)
A local coffee shop in Bandung known as Tentrem Kopi & Kesegaran was established in 2016 located in Cisitu. Cisitu is a small neighborhood inhibited by local people and students from ITB (Institut Teknologi Bandung).Tentrem offers free Wi-Fi and wide variety of drinks, yet it does not provide customers with sofa and air conditioning. Based on the modern coffee shop characteristics, Tentrem has not met the criteria of modern coffee shop. This indicates a gap between customers’ expectation of a coffee shop and what Tentrem actually provides for its customers. Delivering quality service can be seen as an essential strategy in order to survive and success (Dawkins and Reichheld, 1990; Parasuraman, ZeithamI, and Berry, 1985; Reichheld and Sasser, 1990; ZeithamI, Parasuraman, and Berry, 1990). Service quality is pivotal in maintaining customer satisfaction and customer loyalty which can increase profitability of Tentrem. Therefore researcher conducted a multiple linear regression to see the relationship between service quality, customer satisfaction and customer loyalty. The findings are service quality has significant impact on both satisfaction and loyalty, however satisfaction does not act as mediator between service quality and loyalty. Customer satisfaction is also significant for customer loyalty. Keywords: customer, loyalty, satisfaction, services, Tentrem